Stable individual differences in the frequency of chin‐marking behavior across development in the domestic rabbit. (10th May 2022) - Fernández, Yesenia; Arteaga, Lourdes; Zepeda, José Alfredo; Rödel, Heiko G; Hudson, Robyn; Bautista, Amando
Abstract: Individual differences in behavior ("personality") are of considerable interest to behavioral biologists. Important questions include how early in life such differences emerge, what factors influence their emergence, and whether they remain stable across development and into adult life. Given the demanding nature of longitudinal studies, there is a lack of information regarding these questions in mammals. Our aim in this study was to investigate the development of individual differences in chin‐marking behavior (chinning) in the domestic rabbit, a notable part of this species' system of chemical communication, and to relate this to individual differences in growth and behavior among littermates during the early postnatal period. We tested repeatedly the frequency of chinning movements from weaning to sexual maturity in 63 chinchilla‐strain rabbits (35 females, 28 males) from 14 litters. Within litters, we found significant consistencies over time in this behavior, that is, in both sexes inter‐individual differences among litter siblings in the frequency of chinning movements remained stable across the postweaning period until sexual maturity. Unexpectedly, however, we found no significant associations with the morphological, physiological, or behavioral variables known to form a well‐correlated early developmental complex in this species. We tentatively conclude that in the rabbit, individual differences in the frequency of chinning have little relation to other previously studied aspects of individual developmental trajectories. The origin and functional significance of individual differences in chinning frequency, whether in reproductive or other social contexts is largely unknown and requires further investigation. Abstract : In this study, we investigate the development of individual differences in chin‐marking behavior (chinning) in the domestic rabbit and relate this to individual differences in growth and behavior among littermates during the early postnatal period. Individual differences among litter siblings in the frequency of chinning remained stable across the postweaning period until sexual maturity. However, we found no significant associations between individual differences in chinning and individual differences in the morphological, physiological, or behavioral variables known to form a well‐correlated early developmental complex in this species.